THE WEAR RESISTANCE INCREASE OF CHROMIUM CAST IRON - V. M. Ilyushenko; P. Yu. Duvalov; K. E. Baranowski; I. B. Provorova; E. V. Rozenberg (Литьë и металлургия, 2016)
The article presents the results of the tests on the wear resistance of chromium cast irons of different compositions obtained in sand forms. It has been shown that increase of the wear resistance and mechanical properties of the cast iron is possible to obtain using the casting in metal molds. A further increase in wear resistance of parts produced in metal molds is possible by changing the technological parameters of casting and alloying by titanium.